Expression of thioredoxin 1 and peroxiredoxins in squamous cervical carcinoma and its predictive role in NACT - Haiyan Zhu; Xuejiao Tao; Lulu Zhou; Bo Sheng; Xuejie Zhu; Xueqiong Zhu (BMC Cancer, 2019)
Abstract Background This study aims to investigate the expression of thioredoxin 1, peroxiredoxin 1 and peroxiredoxin 2 in bulky cervical squamous carcinoma and its predictive role in cisplatin-based neoadjuvant chemotherapy. Methods Initially, the expression of thioredoxin 1, peroxiredoxin 1 and peroxiredoxin 2 protein was analyzed in 13 human cervical squamous cancer tissues and their paired adjacent non-cancerous tissues by western-blotting and immunohistochemistry. Then, correlation between the expression of thioredoxin 1, peroxiredoxin 1, peroxiredoxin 2 and responses to cisplatin-based neoadjuvant chemotherapy was analyzed in 35 paired tumor samples (pre- and post-chemotherapy) from bulky cervical squamous cancer patients by immunohistochemistry. Results A clinical response occurred in 48.6% (17/35) of patients, including 14.3% (5/35) with a complete response and 34.3% (12/35) with a partial response. The expression of thioredoxin 1, peroxiredoxin 1 and peroxiredoxin 2 was much higher in cervical squamous cancer tissues compared with paired adjacent non-cancerous tissues by western-blotting and immunohistochemistry. Additionally, the expression of thioredoxin 1, peroxiredoxin 1 and peroxiredoxin 2 was significantly up-regulated in post-chemotherapy tissues compared to pre-chemotherapy cervical cancer tissues. High levels of thioredoxin 1, peroxiredoxin 1 and peroxiredoxin 2 were associated with a poor chemotherapy response in cervical squamous cancer patients. Conclusions Thioredoxin 1, peroxiredoxin 1 and peroxiredoxin 2 are frequently over-expressed in cervical squamous cancer. High expression levels of these proteins were related to a poor response to cisplatin-based neoadjuvant chemotherapy. The present study is the first report that thioredoxin peroxidase system may serve as a prediction of the responses to neoadjuvant chemotherapy in cervical squamous cancer.